Rooftop Gardening as A Need for Sustainable Urban Farming: A case of Kathmandu, Nepal - Thapa, Sandesh; Nainabasti, Anjal; Acharya, Sashila; Rai, Neha; Bhandari, Rakshya (International Journal of Applied Sciences and Biotechnology, 2020)
Rooftop gardening is one of the present needs for urban settlement for solving food security problems and promoting sustainable agriculture. To highlight the present status of rooftop gardening in Kathmandu a key informant survey was conducted where 52 respondents were selected where the majority of the rooftop garden maintainers were females (52.8%). All of the respondents have a positive response regarding rooftop gardening and was significant with a year of farming in roofs (χ²= 45, df= 9, P-value=0.000) and the area covered by rooftop farms range from 5-13%. There was a significant monetary value of the soft benefit from rooftop garden as food production (3456.86), air quality (11-19), stormwater retention (20609), and carbon sequestration (6-7) benefits. However, the traditional method was employed to maintain rooftop gardens with planting materials such as plastic bags, pots, and styrofoam carats. Since constraints were recorded in the study area regarding rooftop farming establishment and also is continuing, thus, there should be proper training for the individuals interested in rooftop gardening which enables them to manage and continue their farms more efficiently. Int. J. Appl. Sci. Biotechnol. Vol 8(2): 241-246